2019
DOI: 10.3748/wjg.v25.i36.5569
|View full text |Cite
|
Sign up to set email alerts
|

Long-term growth of intrahepatic papillary neoplasms: A case report

Abstract: BACKGROUNDIntraductal papillary neoplasm of the bile duct (IPNB) is a type of tumor that presents in the intra- or extrahepatic bile ducts. Cystic-type intrahepatic IPNB often mimics simple liver cysts, making the diagnosis difficult. Because the growth of IPNB is slow, careful follow-up and timely therapeutic intervention is recommended. There are few reports with a follow-up period longer than a decade; thus, we report the case of a patient with an IPNB that grew for over 13 years.CASE SUMMARYA 65-year-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…21 ). CEUS is very sensitive for the detection of cystic walls or nodule enhancement [ 42 ]. In contrast to intraductal cholangiocarcinoma, enhancement does not increase in the portal and delayed phases [ 44 ].…”
Section: Cystic Tumoursmentioning
confidence: 99%
“…21 ). CEUS is very sensitive for the detection of cystic walls or nodule enhancement [ 42 ]. In contrast to intraductal cholangiocarcinoma, enhancement does not increase in the portal and delayed phases [ 44 ].…”
Section: Cystic Tumoursmentioning
confidence: 99%
“…Our case was a cystic type IPNB without communication with the biliary tree. Cystic type IPNB has similar imaging features with other cystic liver lesions such as mucinous cystic neoplasms, complicated hepatic cysts, localised Caroli disease [ 13 ]. A communication between the cystic type IPNB and bile duct, or bile duct dilatation can be a clue to differentiate it from other cystic lesions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A communication between the cystic type IPNB and bile duct, or bile duct dilatation can be a clue to differentiate it from other cystic lesions [ 11 ]. Hyperenhancement of the cystic wall or nodules in cystic type IPNB is an important finding for evaluating the potential for malignancy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that recurrence occurred in 13–29% of cases after curative resection, and this proportion increased to 47–62% if the patient had invasive disease [ 17 19 ]. While the classification of IPNB remains complex, meta-analyses and multi-center cohort studies are gradually clarifying the outcomes and prognoses [ 2 , 5 , 6 , 20 , 21 ], and there is also increasing information regarding the surveillance protocols for IPNB and appropriate postoperative follow-up [ 5 , 6 , 22 ]. The present case involved an initial pathological diagnosis of invasive carcinoma with a MUC1-expressing pancreatobiliary type, which is a known prognostic factor.…”
Section: Discussionmentioning
confidence: 99%